An Analysis on Students’ Writing Skill Class IX at MTS Darun Na’im - Helisa; Masrul (Journal of Innovative and Creativity, 2021)
This research consists of problems reseseach objective methods reseach findings and coclusions , This reseach focused on students’ ability to write descriptive text Descriptive text included in the type of text that are not to difficult but still found some difficulties faced by students when writing this eassay, this is the background of reseachers doing this research The purpose of the study is to analyze students’ ability to write descriptive text. In collecting data, reseachers used the writing test as an instrument . This research is a quantitative descriptive study . The components analyzed are idea development ,organizing ideas, grammar , vocabulary , meachanisms , content and punctuation . Reseachers analyzed students’ writing abilities based on five categories : very good , good , sufficient , weak ,lacking and very lacking This reseach was conducted at MTS Darun Na’im class IX . The results of this study illustrate that students face difficulties in organizing and developing ideas. They are not able to develop ideas on the text they write . Whereas the grammar component found no fundamental difficulties The vocabulary component also found some difficulties in applying good English vocabulary and still using Indonesian vocabulary . for the punctuation component, no significant errors were found . Based on the result of this study the teacher is advised to pay more attention to the teaching of this study the teacher is advised to pay more attention to the teaching of descriptive text structures in the development of ideas, idea content , organizing , vocabulary , grammar, mechanisms . Teachers are also expected to provide more examples and exercises on descriptive text to students so that educational goals are achieved well, especially in English subjects